PENANGANAN PERILAKU SISWA BERMASALAH DI SEKOLAH: SEBUAH ANALISIS METODE GURU HANDLING OF PROBLEM STUDENT BEHAVIOR IN SCHOOL: AN ANALYSIS OF THE TEACHER METHOD - Mazrur Mazrur (Jurnal Hadratul Madaniyah, 2022)
During the pandemic, the use of methods to guide students is very helpful for Al-Islam teachers in online learning, because online learning is different from offline learning. In offline learning the teacher can guide directly face to face, but the difference is in online learning Al-Islam teachers have difficulty in guiding students because they cannot meet directly with students. In this case the use of methods in guiding is very helpful for Al-Islam teachers. Method is the means used to achieve the goal. From observations at SMA Muhammadiyah 1 Palangka Raya, they have used this method in guiding students during the pandemic. This discovery aims to find out what methods are used by Al-Islam teachers in overcoming problematic student behavior during the pandemic at SMA Muhammadiyah 1 Palangka Raya.